2012
DOI: 10.1088/0957-4484/23/34/344013
|View full text |Cite
|
Sign up to set email alerts
|

Flexible organic solar cells composed of P3HT:PCBM using chemically doped graphene electrodes

Abstract: Flexible organic solar cells (OSCs) composed of blended films of poly(3-hexylthiophene) (P3HT) and [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) were fabricated and investigated with chemically doped multilayer graphene films as transparent and conducting electrodes on plastic substrates. The sheet resistance of the chemically doped graphene film was reduced to half of its original value, resulting in a significant performance enhancement of OSCs featuring doped graphene electrodes. Moreover, there was no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
74
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(78 citation statements)
references
References 28 publications
3
74
0
1
Order By: Relevance
“…We also tried to discover whether there might be a characteristic length of the side chains at which the electronic properties would remain unchanged; this might be suitable for use as a modeling approach. We chose to study poly(3-hexylthiophene) (P3HT), a polymer widely used in organic devices (Figure 1) [8][9][10][20][21][22][23][24] . This polymer has a hexyl side chain in each monomer unit.…”
Section: Introductionmentioning
confidence: 99%
“…We also tried to discover whether there might be a characteristic length of the side chains at which the electronic properties would remain unchanged; this might be suitable for use as a modeling approach. We chose to study poly(3-hexylthiophene) (P3HT), a polymer widely used in organic devices (Figure 1) [8][9][10][20][21][22][23][24] . This polymer has a hexyl side chain in each monomer unit.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the TFC electrodes are mostly based on PE-DOT [36,70,74,[82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98], graphene (GF) [73,75,[99][100][101][102][103][104][105][106][107][108][109][110][111][112], carbon nanotubes (CNTs) [73,101,102,[106][107][108][109]113], Ag-based nanowires/grids/films [72,[114][115][116][117][118][119]…”
Section: Design Of Flexible Electrodesmentioning
confidence: 99%
“…[8][9][10] For example, Acro et al demonstrated organic solar cells (OSCs) with PCE of only 1.18% based on chemical vapor deposition (CVD) graphene electrode. 8 Meanwhile, stacked multi-layer graphene 11,12 and chemically doped graphene films 13,14 have been used to obtain more conductive graphene electrodes. Wang et al reported OSCs with layer-by-layer stacked graphene anode, in which PCE improved to 2.5%.…”
mentioning
confidence: 99%
“…Lee et al demonstrated OSCs with HNO 3 -doped graphene electrode, which showed PCE of about 2.5%. 13 However, the stability is a challenge for such chemically doped graphene films.…”
mentioning
confidence: 99%